2003
DOI: 10.1038/sj.bmt.1703788
|View full text |Cite
|
Sign up to set email alerts
|

Richter's syndrome after allogeneic stem cell transplantation for chronic lymphocytic leukaemia successfully treated by withdrawal of immunosuppression, and donor lymphocyte infusion

Abstract: Summary:Development of high-grade non-Hodgkin's lymphoma is a possible complication of chronic lymphocytic leukaemia/ small lymphocytic lymphoma, known as Richter's syndrome (RS). Treatment for RS includes systemic chemotherapy and, recently, allogeneic stem cell transplantation (SCT). We describe a patient with B-chronic lymphocytic leukaemia who developed RS 4 months after allogeneic SCT from an HLA-identical sibling. The RS presented with systemic symptoms, lymphadenopathy, pancytopenia and serum lactate de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…14,[33][34][35][36][37][38][39][40] The positive impact of GVHD/GVL on relapse post allograft for CLL is convincingly demonstrated in this analysis. The principle of the antitumor effect of GVH/GVL is employed in the strategy of nonmyeloablative allografting.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…14,[33][34][35][36][37][38][39][40] The positive impact of GVHD/GVL on relapse post allograft for CLL is convincingly demonstrated in this analysis. The principle of the antitumor effect of GVH/GVL is employed in the strategy of nonmyeloablative allografting.…”
Section: Discussionmentioning
confidence: 49%
“…Multiple series have reported promising early results using this strategy for CLL. 15,[37][38][39][40][41][42][43][44][45][46][47][48][49] Safety and feasibility have been demonstrated, along with some evidence of disease control. Although regimen-related toxicity is lower in nonmyeloablative as compared with myeloablative allografting, 15,38 rates of GVHD do not appear dissimilar.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the previous studies, a higher median total cell dose infused (410 Â 10 6 CD3/kg) and development of GVHD improved response. The 2-year OS for the entire cohort was 55% (95% CI: [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. A retrospective analysis by Shaw et al 11 reported on the outcomes of DLI in patients who received TCD with Campath as part of RIC conditioning.…”
Section: Tdli Vs Pdlimentioning
confidence: 99%
“…[52][53][54][55] Two larger series limited to NHL have been published. 52,55 Russell et al 52 reported 17 patients who received DLI after allogeneic HCT (related donor ¼ 15; URD ¼ 2) between 1996 and 2005 for either disease relapse (n ¼ 10) or refractory disease (n ¼ 7).…”
Section: Nhlmentioning
confidence: 99%
“…Its occurrence following allogeneic hematopoietic stem cell transplant (alloHCT) is extremely rare, with only one patient having been reported to date [2]. This patient was treated successfully with withdrawal of immunosuppressive drugs and donor lymphocyte infusion (DLI).…”
mentioning
confidence: 99%